Biogas production from microbial-alkali pretreated corn stover by solid-state anaerobic digestion - Pengxiang, Zhao; Fengjie, Cui; Lingxi, Bu; Jianxin, Jiang (International Journal of Agricultural and Biological Engineering, 2015)
Corn stover pretreated by Ceriporiopsis subvermispora was used as substrate to enhance biogas production via solid state anaerobic digestion (SS-AD). Effects of temperature, inoculum volume and alkaline concentration on the biogas production profermance were investigated. The results showed that pretreatment of corn stover by C. subvermispora benefited the biogas production. The optimal conditions were temperature 35°C, inoculum 10:1 (w/w) and adding 5.0% of alkali, under which the maximum productions were obtained for daily and cumulative biogas of 14.07 L/kg VS and 211.09 L/kg VS. During the SS-AD process, the total solids (TS) and volatile solid (VS) were significantly degraded. The volatile fatty acids (VFA) concentration increased to 106 mmol/L and alkalinity decreased by about 23%. The results collectively suggested that microbial-alkali pretreatment of corn stove combining mesophilic condition could be a promising way to produce biogas in SS-AD. Keywords: solid-state anaerobic digestion, corn stover, Ceriporiopsis subvermispora, microbial-alkali pretreatment, biogas production DOI: 10.3965/j.ijabe.20150805.2032 Citation: Zhao P X, Cui F J, Bu L X, Jiang J X. Biogas production from microbial-alkali pretreated corn stover by solid-state anaerobic digestion. Int J Agric & Biol Eng, 2015; 8(5): 96－104.